The VI Nav cards: a holistic approach to supporting the design of navigation aids for the blind and visually impaired - Yehia, Ziyad Khamis Mohammad (2020)
The Royal National Institute for Blind People (RNIB) estimates that there are around two million Blind and Visually Impaired (B/VI) people in the UK. Due primarily to the general ageing of the population, this number is expected to increase to four million by 2050. Previous research has highlighted that B/VI people frequently experience problems with their mobility and thus desire improved means for travel and navigation. As a consequence, researchers and industry put much effort into producing a range of navigation aids. Nevertheless, there is considerable evidence that such supporting mechanisms typically fail to satisfy the wide range of needs that B/VI people have for their aids, and thus tend to have low adoption rates.